Effect of prior eccentric exercise on the VO2 kinetics during heavy cycling exercise in male basketball players - Stasiulis, A.; Dubininkaite, L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The oxygen uptake (VO2) kinetics may vary with work rate or under different conditions of exercise e.g. prior exercise. The aim of this study was to examine the influence of prior drops without jumps on VO2 kinetics during heavy cycling exercise in male basketball players. Methods: Eight male basketball players of national level (age 19,5 ± 0,53 yr, height 191,0 ± 5,8 cm, and weight 86,5 ± 9,78 kg) volunteered to participate in this study. Subjects completed four protocols on separate days. During the first day they performed continuous increasing cycling exercise (ICE). In the second examination the subjects performed constant cycling exercise (CCE) with which consisted of 3 min unloaded cycling, 9 min cycling with intensity in the middle between maximal oxygen uptake (VO2peak) and first ventilatory threshold (79.5 ± 2.5 % of VO2max) and 3 min of unloaded cycling. In the third examination the subjects performed one hundred drops from 0.47 m height with eccentric contractions of thigh muscles at the end every 20 s (D), rested passively for one hour and then performed CCE. Following 24 hours the fourth examination was performed using the same protocol as in the second one. Testing was performed on mechanically braked cycle ergometer (Monark 834E) while cycling at 70 rpm. At the end of each 9 min CCE, a blood sample was collected from the finger tip for immediate analysis of blood lactate concentration ([lactate]). Rating f perceived exertion was evaluated by the subject at the end of each CCE, and muscle pain was assessed on the next day after eccentric exercise. Pulmonary gas exchange was measured breath-by-breath throughout all tests. VO2peak was determined as the highest value in 15 s period before the subjects` volitional termination of the ICE. The VO2 response during exercise and recovery periods of CCE was fitted the bi-exponential function. The first 20 s were always removed from the analysis. In addition the slow component was calculated as the difference between the end exercise VO2 and the 3rd min VO2. Results: Prior eccentric exercise had no effect on time constants of VO2 response during on- and off-transitions during CCE. The VO2 values at the 3rd, 6th and 9th min of CCE did not change significantly during all examinations. The rating of perceived exertion was slightly but not significantly elevated at the end of CCE one hour and 24 hours after eccentric exercise. The subjects felt moderate muscle pain (4,0 ± 2,9) 24 hours after eccentric exercise. Discussion/Conclusion The prior eccentric exercise did not cause any change of VO2 kinetics during heavy CCE in male basketball players despite augmented efforts and muscle pain. This may be associated with adaptation of basketball players to such kind of activities which are often involved in their training process.